2018
DOI: 10.1093/gbe/evy009
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Adaptive Evolution and Relaxed Constraints in Sex-Biased Genes of South American and West Indies Fruit Flies (Diptera: Tephritidae)

Abstract: Several studies have demonstrated that genes differentially expressed between sexes (sex-biased genes) tend to evolve faster than unbiased genes, particularly in males. The reason for this accelerated evolution is not clear, but several explanations have involved adaptive and nonadaptive mechanisms. Furthermore, the differences of sex-biased expression patterns of closely related species are also little explored out of Drosophila. To address the evolutionary processes involved with sex-biased expression in spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 117 publications
6
19
0
Order By: Relevance
“…For example, the pattern in Gryllus (Fig. 3) is consistent with observations of rapid evolution of testis-biased and slow evolution of ovary-biased genes in Drosophila [7,11,14,61] (see also results in a related fly, [37] ). In addition, this pattern also matches our recent results from beetles (Tribolium castaneum) that showed rapid evolution of testis-biased genes [13], a taxon which like Drosophila species' is polyandrous, and has evidence of pre-and post-mating female choice mechanisms [84].…”
Section: Rapid Evolution Of Testis-biased Genessupporting
confidence: 86%
See 1 more Smart Citation
“…For example, the pattern in Gryllus (Fig. 3) is consistent with observations of rapid evolution of testis-biased and slow evolution of ovary-biased genes in Drosophila [7,11,14,61] (see also results in a related fly, [37] ). In addition, this pattern also matches our recent results from beetles (Tribolium castaneum) that showed rapid evolution of testis-biased genes [13], a taxon which like Drosophila species' is polyandrous, and has evidence of pre-and post-mating female choice mechanisms [84].…”
Section: Rapid Evolution Of Testis-biased Genessupporting
confidence: 86%
“…However, there is a striking paucity of data on the relationship between sex-biased expression in the brain and protein sequence evolution [22]. Moreover, the minimal research available from birds, humans and flies have suggested different types of male and female effects on rates of protein evolution, depending on the system [23,29,32] (see also some brain-related and composite-tissue analyses [36,37]), and the causes of those patterns remain poorly understood. It is therefore evident that additional study is needed of sex-biased brain expression and its relationship to molecular…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our results for the higher Diptera, for instance, Katzourakis et al ( 2001) found evidence for a correlation between sexual selection and species richness in hoverflies. Similar conclusions have been drawn in a study of tephritid species (Congrains et al, 2018), which aligns taxonomically more closely with our findings of parallel sex biased gene…”
Section: Possible Links Between Enhanced Gene Duplicate Accumulationsupporting
confidence: 92%
“…Consistent with our results for the higher Diptera, Katzourakis et al (2001) found evidence for a correlation between sexual selection and species richness in hoverflies. Similar conclusions have been drawn in a study of tephritid species (Congrains et al, 2018), which aligns taxonomically more closely with our findings of parallel sex biased gene duplications in schizophoran lineages outside the Drosophilidae. Based on artificial breeding experiments, however, sexual conflict was concluded to play no role in reproductive isolation in D. pseudoobscura (Bacigalupe et al, 2007).…”
Section: Possible Links Between Enhanced Gene Duplicate Accumulationsupporting
confidence: 92%